Endoscopic Findings in Patients with Moderate to Severe COVID-19: A Cross-sectional Study - Parra Izquierdo, Viviana; Frías Ordoñez, Juan Sebastián; Navarro Morantes, Jenny Paola; Navarro Morantes, Humberto; Castro Ruíz, Kimberly Tatiana; Navarro Morantes, Cristina; Castillo, Jesús David; Flórez Sarmiento, Cristian (Revista colombiana de Gastroenterología, 2023)
Introduction: SARS CoV-2 infection has diverse gastrointestinal manifestations, which on many occasions require endoscopy. Objective: The primary objective is to describe the need for endoscopic procedures from a sample of hospitalized patients with moderate to severe COVID-19, and the secondary objective is to describe in detail the characteristics, findings and interventions. Materials and methods: descriptive observational cross-sectional study during May 2020 to December 2021, about indications, endoscopic findings, interventions, anesthesia requirement and adverse events, from a sample of patients with moderate to severe COVID-19 in whom gastrointestinal endoscopic procedures were performed for any indication. Results: of 2312 hospitalized patients with moderate to severe COVID-19, 2.72% required endoscopic procedures, with a predominance of men (75%), mean age 65.7 years, and the majority for upper gastrointestinal endoscopy (68%). The most frequent indications were gastrointestinal bleeding (62%) and enteral access (28.3%). Ischemic compromise was documented in three patients. In those with gastrointestinal bleeding, 9.5% required hemostatic therapy. 65% were on ventilatory support and sedation at the time of the endoscopic procedure, and in half of these cases anesthesiology support was required, with no peri-procedural adverse events, and no need for negative pressure room in any procedure. Conclusions: In patients with moderate-severe COVID-19 and requiring gastrointestinal endoscopy, clinical judgment is required to define the pertinence of the procedure, and in many cases conservative management can be considered.